Feminisme Liberal dalam Anime Kidō Senshi Gandamu Tekketsu No Orufenzu Karya Tatsuyuki Nagai - Putra, I Made Dwi Christian Gustiana (Vocational College of Diponegoro University, 2021)
This research is entitled